2020
DOI: 10.1029/2020gl090360
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Electron Microbursts as High‐Energy Tail of Pulsating Aurora Electrons

Abstract: In this study, by simulating the wave-particle interactions, we show that subrelativistic/ relativistic electron microbursts form the high-energy tail of pulsating aurora (PsA). Whistler-mode chorus waves that propagate along the magnetic field lines at high latitudes cause precipitation bursts of electrons with a wide energy range from a few kiloelectron volts (PsA) to several megaelectron volts (relativistic microbursts). The rising tone elements of chorus waves cause individual microbursts of subrelativisti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 50 publications
(92 reference statements)
17
83
0
Order By: Relevance
“…Figure 13b and 13c show that LBC waves at a frequency of ∼1 kHz coincided with the electron-flux enhancement. Because LBC waves are known to scatter electrons with energies of kiloelectronvolts to tens of kiloelectronvolts and cause diffuse aurora (e.g., Miyoshi et al, 2015Miyoshi et al, , 2020Thorne et al, 2010), they may have caused the observed increase of electron flux at energies of 10-20 keV with pitch angles near the loss cone and intensified the 557.7-nm emission at the equator edge of the diffuse aurora.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 13b and 13c show that LBC waves at a frequency of ∼1 kHz coincided with the electron-flux enhancement. Because LBC waves are known to scatter electrons with energies of kiloelectronvolts to tens of kiloelectronvolts and cause diffuse aurora (e.g., Miyoshi et al, 2015Miyoshi et al, , 2020Thorne et al, 2010), they may have caused the observed increase of electron flux at energies of 10-20 keV with pitch angles near the loss cone and intensified the 557.7-nm emission at the equator edge of the diffuse aurora.…”
Section: Discussionmentioning
confidence: 99%
“…The link between pulsating aurora and relativistic microbursts is observationally elusive, but has been theoretically proposed. Recent test-particle simulations by Chen et al (2020) and Miyoshi et al (2020) show that whistler-mode chorus rising tone elements can scatter keV-MeV microburst electrons. Miyoshi et al (2020) went on to hypothesize that relativistic microbursts are the high-energy tail of pulsating aurora.…”
mentioning
confidence: 99%
“…Their theory showed that relativistic electron (>500 keV) precipitation should have a positive energy dispersion (higher-energy electrons are precipitated later) following a negative energy dispersion of the low energy component (lower energy electrons are precipitated later). Miyoshi et al (2020) proposed a hypothesis stating that relativistic electron microbursts have the same origin as the pulsating aurora. That is, chorus waves cause electron scattering in a wide energy range from a few keV to more than several MeV if the chorus waves can propagate to higher latitudes.…”
mentioning
confidence: 99%